Dietary Supplementation of Oregano and Sage Dried Leaves on Performances and Meat Quality of Rabbits - Luca Rotolo; Francesco Gai; Silvana Nicola; Ivo Zoccarato; Alberto Brugiapaglia; Laura Gasco (Journal of Integrative Agriculture)
The aim of this research was to evaluate the dietary supplementation 1% (w/w) of oregano and sage dried leaves on performances and meat quality of broiler rabbits. A feeding trial, which lasted 48 d, was carried out on 105 male Bianca Italiana rabbits randomly divided in seven groups and fed ad libitum. At the end of the trial ten animals per group were slaughtered and samples of dorsal muscle were taken in order to perform laboratory analysis. Mortality rate did not statistically differ between groups. Growth performances of animals fed diets supplemented with aromatic plants were higher (P<0.05) than those of animals of control group, whereas carcass parameters were not affected by treatments excepting for the slaughter weight that showed the same trend as growth performances. Meat quality traits, oxidative lipid stability and fatty acid profile were not influenced by aromatic plant supplementation. In conclusion, oregano and sage in form of dried leaves can be used in rabbit without adverse effects on performance, carcass characteristics and meat quality traits.